The Impact of Recruitment and Training Strategies on Enhancing the Efficiency of Strategic Tourism Alliances: An Exploratory Study of a Sample of Tourism Companies in Baghdad - Firas Naji Hatem (Indonesian Journal of Law and Economics Review, 2026)
General Background: The tourism sector increasingly depends on strategic alliances to address competition and resource-sharing challenges. Specific Background: The effectiveness of these alliances is strongly linked to the quality of human resources managing partnerships. Knowledge Gap: Many tourism companies prioritize legal and financial aspects while neglecting recruitment and training strategies. Aims: This study examines the relationship between recruitment and training strategies and strategic alliance efficiency in Baghdad tourism companies. Results: Based on 93 valid responses, the findings show a strong positive correlation (0.800) and significant effect, with these strategies explaining 63% of alliance efficiency, where technical and behavioral training contributes the most. Novelty: The study connects human resource strategies with alliance performance in the tourism context. Implications: Aligning recruitment and training with partnership requirements can strengthen cooperation, reduce conflicts, and support better service outcomes. Highlights:• Strong Statistical Association Identified Between Human Resource Practices and Alliance Performance• Training Focused on Behavioral and Technical Skills Shows Highest Contribution to Partnership Stability• Digital Talent Acquisition Supports Coordination but Remains Secondary Compared to Skill Development Keywords: Recruitment Strategies, Training Programs, Strategic Alliances, Tourism Companies, Alliance Efficiency.